Cryphodera lithocarpus sp. nov. (Nematoda: Heteroderidae), a new species of cystoid nematode from roots and surrounding soil of Lithocarpus uvariifolius in Guangdong, China - Ni, Chun-Hui; Cheng, Wen-Hao; Zhang, Run; Xu, Chun-Ling; Xie, Hui (Zootaxa, 2026)
Cryphodera lithocarpus sp. nov., collected from roots and rhizospheric soil of Lithocarpus uvariifolius in Guangdong province, China. The new species was characterized by having the female nearly spherical, labial region offset, stylet length 38.9 (37.4–40.3) μm, vulval lips protruding, area between vulva and anus concave, vulva–anus distance 52.3 (31.1–62.7) μm; second stage juvenile with 2 lip annules, stylet length 30.7 (28.4–32.4) μm, lateral field areolated with 3 incisures, tail 60.5 (49.6–68.0) μm long, with narrow rounded terminus, hyaline region 31.7 (24.0–39.2) μm long and hyaline region approximately equal to stylet. The new species was close to C. guangdongensis, C. sinensis and C. japonicum. The phylogenetic trees based on the ITS-rRNA, 28S-rRNA D2-D3 region and the partial COI gene sequences showed that the new species clustered with Cryphodera species but with separate species status. A key to the species of the genus Cryphodera is also provided in this study.